An Advanced Microturbine System with Water-Lubricated Bearings - Susumu Nakano; Tadaharu Kishibe; Tomoaki Inoue; Hiroyuki Shiraiwa (International Journal of Rotating Machinery)
A prototype of the next-generation, high-performance microturbine system was developed for laboratory evaluation. Its unique feature is its utilization of water. Water is the lubricant for the bearings in this first reported application of water-lubricated bearings in gas turbines. Bearing losses and limitations under usage conditions were found from component tests done on the bearings and load tests done on the prototype microturbine. The rotor system using the water-lubricated bearings achieved stable rotating conditions at a rated rotational speed of 51,000 rpm. An electrical output of 135 kW with an efficiency of more than 33% was obtained. Water was also utilized to improve electrical output and efficiency through water atomizing inlet air cooling (WAC) and a humid air turbine (HAT). The operation test results for the WAC and HAT revealed the WAC and HAT operations had significant effects on both electrical output and electrical efficiency.